Pelatihan Pembuatan Alat Peraga Motor Listrik Dan Pembangkit Listrik Tenaga Surya Sederhana Kepada Siswa Di SMA Yadika 9 Bekasi - Taat Guswantoro; Faradiba Faradiba; Nya Daniaty; Manogari Sianturi; Septina Severina Lumbantobing; Ngia Masta; Jei Tipoani Sinaga; Yufran Meliando Olla; Yonas Firdinal Silaban; Piter Honirius Naitaunus; Bintang R. Simbolon; Erni Murniarti (Jurnal Pengabdian Masyarakat Nusantara, 2024)
Props play an important role in learning because they can increase student understanding and involvement. The Physics Education Study Program FKIP UKI has the specialty of making teaching aids from simple materials, so that the Tri Dharma of Higher Education activities are adapted to the development of teaching aids. Responding to the school's request, the Physics Education Study Program FKIP UKI held training in making electric motor props and simple solar power plants for students at SMA Yadika 9 Bekasi. This training carried out a demonstration of making props followed by direct practice by a group of students. Student responses, measured through questionnaires, showed positive perceptions of the material (79.54%), effectiveness of instructor (81.02%), and overall satisfaction (79.78%). Suggestions for future training include diversifying materials, using props that are relevant to technology, and holding interclass competitions in making props.